Calotropis procera mediated one pot green synthesis of Cupric oxide nanoparticles (CuO-NPs) for adsorptive removal of Cr(VI) from aqueous solutions - Dubey S.; Sharma Y.C. (My University, 2025)
The present study deals with the synthesis of CuO-NPs via green route and investigated its application for removal of Cr(VI) from aqueous solutions. The experimental parameters were optimized through Box–Behnken Design (BBD) of response surface methodology for the optimum response. The adsorption equilibrium data was well fitted to Freundlich isotherm model and the kinetics was explained through pseudo-second-order kinetic model. The overall process was feasible, spontaneous and exothermic. Linear approach for analysing the isotherm as well as kinetic parameters was found more appropriate than the non-linear approach. The adsorbent was successfully regenerated and reused up to five consecutive cycles without significant loss in removal capacity. The experimental results exhibited that CuO-NPs can be a good alternative for Cr(VI) removal from aqueous solutions. Copyright © 2017 John Wiley & Sons, Ltd.